Critic on Auguste Comte’s Positivism in Sociology (An Islamic Sociology Perspective) - Novita Sari; Jarman Arroisi (POSTGRADUATE OF PALANGKA RAYA STATE ISLAMIC INSTITUTION, 2020)
The rapid science in the modern era, provides significant changes for humans, both in the fields of economics, politics, culture, environment, society, education, and even religion. The 19th century is a century of science that is growing rapidly, this can be seen from the emergence of various scientists who provide concepts, theories based on philosophy with basic ontology, epistemology, and axiology as a contribution to the development of science. One of them, the scientist known as the father of sociology, was Auguste Comte a scientist from France. Comte is famous for its philosophy of postivism because of the many references by scientists in the contemporary era. This is based on the calculation of the success of designing the social structure of modern humans with three stages of law, but one side of the theory he produced has eliminated the fundamental value in humans, namely eliminating the metaphysical basis. In a three-stage law, more concerned with physical values than metaphysical values, this will result in a society that abandons religion and even eliminates the existence of God. The thoughts produced by Comte are thoughts originating from the west, where the basic West is relativism so if viewed from an Islamic point of view this theory will produce atheists and eliminate the sanctity of religion. In Islam religion and society are inseparable because religion is a guideline that is used as a basis in people's lives based on the values of the Qur'an and Sunnah. Therefore in this paper we will study more deeply the criticisms of Aguste Comte's thinking, using qualitative research types, with descriptive analysis methods and theological philosophical approaches.